ANALISIS NILAI TUKAR PETANI SEBAGAI INDIKATOR KESEJAHTERAAN PETANI BAWANG MERAH (SUATU KASUS PADA KELOMPOK TANI MEKAR JAYA DI DESA TONJONG KECAMATAN KRAMATWATU KABUPATEN SERANG) - Rafif Raihan Pandunusa; Aris Supriyo Wibowo; Sulaeni Sulaeni (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2023)
This research was to analyze the exchange rate of shallot farmers in The Mekar Jaya Farmer’s Group in Tonjong Village, Kramatwatu District, Serang Regency. The Type of research used in this research was descriptive analysis research. The research instrument used in this research was questionnaire. Methods of data collection by observation, interviews and literature study. The sample of this research were 31 Farmers in Mekar Jaya Farmer’s Group in Tonjong Village. The sampling technique used in this research use a simple random sampling technique that is proportional to the land area. The data processing in this study use an analysis of the calculation of the farmer's exchange rate, namely the total farmers' income divided by the total farmer expenditures multiplied by 100, with the indicator if the result is NTP > 100 means the farmer has a surplus, NTP = 100, it means the farmer breaks even, NTP < 100, means the farmer experiences deficit. Based on the results of the analysis that has been carried out, it is found that the exchange rate of shallot farmers in the Mekar Jaya farmer’s group in Tonjong Village, Kramatwatu District, Serang Regency is 149,848 with a total farmer income of 1,325,200,000 and a total farmer expenditure of 884,361,000 which means farmers have a surplus. This condition shows that the shallot farmers in the Mekar Jaya farmer group in Tonjong Village are in a prosperous condition.